SAVINGS AND LOANS SYSTEM IN COOPERATION WITH SMK 41 USING VISUAL BASIC 6.0 - Margaretha Ratna Dewi; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2005)
Cooperative association is an organization based on the principle of kinship.Therefore, the school was made co-schools include 41 vocational schools located inJl. Zoo Kingdom comp tin, Pondok Labu. This cooperative provides several businessunits, one of them is a savings and loan.In carrying out its activities, sometimes have a problem when a member wants to saveor to get a loan. Because there are some members who do not understand do not evenunderstand the rules that already exist, so that it can inhibit or slow in submitting thereport.With the new system has been computerized to assist cooperatives in addressing theproblem, so that cooperatives can accurately, quickly and accurately in processingand obtaining data